(untitled) (Texas Journal of Engineering and Technology, 2026)
In this paper we have considered the problem of implementation of virtual physics labs in higher education institutions, as well as their advantages and disadvantages compared to traditional laboratory practical’s. The importance of supplementing real experiments with virtual ones is highlighted. It is shown that the virtual laboratory is one of the innovations having a significant impact on the modern education system. The virtual laboratory provides practical training with all the existing limitations, such as the tools and materials of practical equipment at universities